CDIO IDEOLOGY IN MATH TRAINING - Yuliya V. Vainshtein; Viktoriya A. Shershneva; Konstantin V. Safonov (Moscow Polytechnic University, 2016)
The article presents the methods to improve the quality of mathematics education of future bachelors of engineering majors. The influence of CDIO ideology on teaching engineering students mathematical disciplines is analyzed. The authors put the main emphasis on teaching mathematics from the standpoint of world standards CDIO basing on polyparadigmal approach, which complies with the Federal state educational standard of higher education. It is offered to fill the gaps in determining the quality of mathematical preparation of future bachelors of engineering majors in the federal state educational standards of higher education with additional competencies based on CDIO ideology. The authors dwell on the features of context education, interdisciplinary integration, project implementation, activities students, reflective and evaluative students' activities, teamwork in math learning in an electronic environment Moodle within CDIO ideology.